Design of A Portable Trainer Simulation of Coal Distribution and Boiler Water Control Process in PLTU Based on PLC - Suwarti, Suwarti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
The purpose of this research is to simulate the coal distribution process using a conveyor and water regulation in the boiler whose program is made using PLC-based CX-Programmer software. The first method used in the conveyor work process is to install several lights and 2 motors on each conveyor as many as 5 conveyors are connected with a timing belt as an indicator that the conveyor is working. The second method used in the simulation of water regulation in the boiler is almost the same as the conveyor system, namely by installing several motors and lights as indicators of the boiler working, as well as adding a high/medium/low sensor to adjust the water level. The conveyor and boiler systems work automatically using PLC devices that have been programmed through the CX-Programmer. In the 3-phase (reverse-forward) motor load test, the following data were obtained: PLC input voltage is 224 Volts, V line voltage is 396 Volts, motor input voltage is 398 Volts, and motor current is 1,6 Ampere. The result of this research are used as additional measurable equipment in the energy conversion laboratory which previously amounted to 2 test equipment into 3 test equipment.